Crack Avoidance by Using Titanium as Filler Material for Laser Welding of a Chromium Steel with a Nickel Alloy - Karaaslan, Ahmet (WALTER DE GRUYTER GMBH, 2008)
Crack Avoidance by Using Titanium as Filler Material for Laser Welding of a Chromium Steel with a Nickel Alloy. The present contribution highlights the welding procedure with and without filler material and the properties of laser welding of a high alloyed Chromium steel with a Nickel alloy. Characterization of the test weld properties has been carried out by Vicker's hardness measurements. Investigations of the microstructure of the weld seam and HAZ have been realized by scanning electron microscopy and light microscopy and the chemical compositon of the weld seam has been determined by EDX-analysis. During welding with Titanium as filler material hot cracking could be avoided, while cracking appeared in the weld centerline during welding without filler material.
Keywords: Materials Science